Courtyard of Our Lady of Bethlehem Church - Mumbai Archive Project Team (Jio Institute, 2024)
Our Lady of Bethlehem church has a large open courtyard paved with gravestones. On special occasions, such as festival days, the additional congregation is accommodated in the courtyard.